Effect of Halide Concentration on the Effectiveness of Banana Peel Waste Inhibitor at 60C - Widodo, Mochamad Puji; Tua Silaen, Yohannes Marudut; Ahada Kuswara, Muhammad Faiq Ridho; Rohmannudin, Tubagus Noor (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2019)
Organic inhibitors have been widely studying to be an alternative corrosion prevention because of its abundance and non-hazardous effect to the environment. One of organic inhibitors which is obtained from plant extract is banana (Musa Paradisica) peel, because it has gallocatechin which is a strong antioxidant. Otherwise, inhibition effectiveness from organic compound decreases during increasing of temperature. However, the addition of other substance like halide ion has provided multiple effect of corrosion inhibitor effectiveness. The addition of the halide ions can enhanced the inhibition efficiency of the organic inhibitors. This research highlights the effect of additional halide concentration to the inhibition effectiveness of Musa Paradisica (banana) peel on API 5 L steel in 3,5% NaCl at temperature 600C. This inhibition performance is investigated using weight loss measurement and electrochemical measurement. Result shows that the maximum inhibition efficiency was observed with the mixture of 500 ppm banana peel waaste extract and 100 ppm potassium iodide at 600C. Also, The blends behaved as mixed type inhibitor. The effectiveness was found to be in order of KI > KBr due to the larger ionic radius in iodide ion.